1999
DOI: 10.1046/j.1365-294x.1999.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and postglacial dispersion of the chub (Leuciscus cephalus) in Europe

Abstract: A phylogeographic analysis of mitochondrial DNA variation was performed in order to test the hypothesis of a postglacial recolonization of mid- and north-European rivers from a Danubian refuge. Over 345 chub specimens from European rivers covering most of the species' native range were investigated using 600 bp of the cytochrome b gene. Chub in European rivers belong to four highly divergent mitochondrial groups (lineages) differing by mean divergence estimates from 5.2% to 7.89%. These four lineages have a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
242
2
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(276 citation statements)
references
References 54 publications
29
242
2
3
Order By: Relevance
“…They showed that the species is subdivided into deeply divergent Western and Eastern phylogroups which are not, however, distinct species (Lajbner et al, 2010). Also in other freshwater species, including the chub (Leuciscus cephalus) (Durand et al, 1999), perch (Perca fluviatilis) (Nesbø et al, 1999) and barbel (Barbus barbus) (Kotlik and Berrebi, 2001), genetic lines related to the geographical location were observed which could indicate an evolutionary history common to different freshwater species. On the basis of the haplogroup composition, composite haplotype distribution and population location, it can be inferred that the haplogroup A observed in the present study corresponds to the Western phylogroup reported by Lajbner et al (2007 while the haplogroup B corresponds to the Eastern phylogroup.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the species is subdivided into deeply divergent Western and Eastern phylogroups which are not, however, distinct species (Lajbner et al, 2010). Also in other freshwater species, including the chub (Leuciscus cephalus) (Durand et al, 1999), perch (Perca fluviatilis) (Nesbø et al, 1999) and barbel (Barbus barbus) (Kotlik and Berrebi, 2001), genetic lines related to the geographical location were observed which could indicate an evolutionary history common to different freshwater species. On the basis of the haplogroup composition, composite haplotype distribution and population location, it can be inferred that the haplogroup A observed in the present study corresponds to the Western phylogroup reported by Lajbner et al (2007 while the haplogroup B corresponds to the Eastern phylogroup.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of a limited sampling for the Caucasus region, our results strongly support the existence of a particular lineage in this region which is well separated from all the other populations. The existence of a refuge in the Caspian/Caucasian region has already been proposed for different European temperate species (Durand et al, 1999;Deffontaine et al, 2005), but it is difficult to be more precise about such a lineage without better sampling in this region and in the neighbouring areas.…”
Section: Glacial Refugesmentioning
confidence: 99%
“…However, there was already a connection between the Anatolian landmass and Central Asia during the early Oligocene (34-32 MYA) (Popov et al, 2004). While many authors have studied the biogeography of freshwater fishes within Europe (Durand et al, 1999;Zardoya & Doadrio, 1999;Perdices & Doadrio, 2001;Durand et al, 2003;Perdices et al, 2003;Ketmaier et al, 2004;Bohlen et al, 2006a;Perdices et al, 2008), there are only a few studies referring to the relationship between European and Asian freshwater fishes (Bǎnǎrescu, 1989(Bǎnǎrescu, , 1992Zardoya & Doadrio, 1999;Perdices & Doadrio, 2001;Kohlmann et al, 2003;Bohlen et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%